Characterization of biofilm formation, pyocyanin production, and antibiotic resistance mechanisms in drug-resistant Pseudomonas aeruginosa isolated from children in Egypt - Maram M. S. El-Shahed, Dina E. Mahmoud, Noha S. Soliman, Yasmin A. ElMahdy, Sara H. Mohamed (Journal of Applied Pharmaceutical Science, 2020)
Children can be exposed to more bacterial infections, which has become of importance, especially when bacteria resist many of the antibiotics used today. Twelve Pseudomonas aeruginosa strains were collected and identified. Antibiotic sensitivity testing, biofilm formation, and pyocyanin production were evaluated. A cluster analysis was performed. Phenotypic and genotypic detection of efflux pump activity and Metallo-β Lactamase (MβLs) resistance mechanisms were studied. A marked resistance (100%) resulted toward antibiotics including cefotaxime, cefoxitin, ceftriaxone, and meropenem. Imipenem and amikacin antibiotics showed sensitivity percentages of 41.7 and 33.3, respectively. 66.7% were able to form a biofilm at which they were categorized as moderate (25%) and weak (41.7%). Phenotypically, 41.67% of the isolates were MBL metallo-β-lactamase-positive, but genotypically, blaVIM gene was detected only in one isolate, while blaIMP was not detected in any isolate. MexR and MexZ genes were detected in all isolates (100%). NfxB gene and MexT gene were found in 27.27% and 45.45% of isolates, respectively. All the efflux genes were found collectively in three isolates. This study highlights the occurrence of antibiotic resistance, besides the production of important virulence factors (biofilm formation and pyocyanin production). Also, the gene occurrence of antibiotic resistance mechanisms was reported among our P. aeruginosa. This virulent bacterial behavior is alarming which needs attention to the way we use antibiotics.
Keywords: Pyocyanin, biofilm, MBLs, effluxpump, Pseudomonas aeruginosa.